Potentiation of Natural Killer Cells for Cancer Immunotherapy: A Review of Literature - Lowry, Lacy E.; Zehring, William A. (Frontiers in Immunology, 2017)
It is widely acknowledged that the human immune system plays a crucial role in preventing the formation and progression of innumerable types of cancer. The mechanisms by which this occurs are numerous, including contributions from both the innate and adaptive immune systems. As such, immunotherapy has long been believed to be an auspicious solution in the treatment of malignancy. Recent research has highlighted the promise of natural killer cells as a more directed immunotherapy approach. This paper will focus on the methods of potentiation of natural killer cells for their use in cancer therapy.